2023
DOI: 10.1097/jom.0000000000002785
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Sampling Study on SARS-CoV-2 Contamination of Air and Surfaces in a Large Meat Processing Plant Experiencing COVID-19 Clusters in June 2020

Abstract: Comprehensive environmental sampling showed limited SARS-CoV-2 contamination of air and surfaces in a meat processing plant, despite a large proportion of workers testing SARS-CoV-2 positive. A strict COVID-19 policy was in place, suggesting that SARS-CoV-2 transmission may be controlled in meat processing plants by enforcing appropriate preventive and mitigation measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Estimates of genome copies per cm 2 of SARS-CoV-2 RNA positive surface samples were calculated using a standard curve with no sample collected exceeding 6.6×10 3 genomic copies/cm 2 . While finding limited amounts of SARS-CoV-2 nucleic acid at sites reporting a COVID-19 cases may seem counter-intuitive, low levels of contamination were reported in similar studies including the in areas recently occupied by symptomatic workers (Gholipour et al ., 2020; Marshall et al ., 2020; Mouchtouri et al ., 2020; Cherrie et al ., 2021; Marcenac et al ., 2021; de Rooij et al ., 2023) and in some clinical settings occupied by infected patients (Ryu et al ., 2020; Goel et al ., 2022; Warren et al ., 2022). Two control sites were also sampled as part of this study; both positive and suspected positive samples were identified at these sites albeit at lower levels than in recruited sites.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of genome copies per cm 2 of SARS-CoV-2 RNA positive surface samples were calculated using a standard curve with no sample collected exceeding 6.6×10 3 genomic copies/cm 2 . While finding limited amounts of SARS-CoV-2 nucleic acid at sites reporting a COVID-19 cases may seem counter-intuitive, low levels of contamination were reported in similar studies including the in areas recently occupied by symptomatic workers (Gholipour et al ., 2020; Marshall et al ., 2020; Mouchtouri et al ., 2020; Cherrie et al ., 2021; Marcenac et al ., 2021; de Rooij et al ., 2023) and in some clinical settings occupied by infected patients (Ryu et al ., 2020; Goel et al ., 2022; Warren et al ., 2022). Two control sites were also sampled as part of this study; both positive and suspected positive samples were identified at these sites albeit at lower levels than in recruited sites.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into MPP COVID‐19 outbreaks found aerosols were the primary route of SARS‐CoV‐2 transmission among MPP workers (Günther et al, 2020; Pokora et al, 2021). SARS‐CoV‐2 has been detected on fomites in MPP, which represent another potential route of virus transmission and SARS‐CoV‐2 has been shown to on persist various abiotic surfaces under various conditions (Biryukov et al, 2020; Chin et al, 2020; De Rooij et al, 2023; Gidari et al, 2021; Harbourt et al, 2020; King et al, 2020; Kwon et al, 2021a; Pastorino et al, 2020; Riddell et al, 2020; Van Doremalen et al, 2020; Wing et al, 2022). A decrease in temperature correlates with increased persistence of viable SARS‐CoV‐2 on abiotic surfaces while very low (20% or less) and very high (80% or more) relative humidity increases virus inactivation and average (20–80%) relative humidity prolongs virus persistence (Biryukov et al, 2020; Kwon et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%